2007
DOI: 10.1007/s15010-007-7153-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Oxygen Molecules in Meningitis-Associated Labyrinthitis and Hearing Impairment

Abstract: Pneumococcal meningitis remains a serious disease with a case fatality rate of 15%-25%. Furthermore, long-term residues affect up to 50% of survivors. One of the most frequent sequelae is sensorineural hearing loss, which occurs in 26% of survivors of pneumococcal meningitis. Unfortunately, sufficient treatment regimens are still missing. New insights into the pathology and pathophysiology of meningitis-associated hearing loss have come from animal models of bacterial meningitis. Most likely, bacteria reach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 101 publications
1
33
0
Order By: Relevance
“…Hearing loss during pneumococcal meningitis may result in part from the production of highly reactive oxygen species (ROS) (31). Treatment with rifampin has been shown to decrease the level of ROS compared to ceftriaxone in an experimental meningitis model in rabbits (9).…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss during pneumococcal meningitis may result in part from the production of highly reactive oxygen species (ROS) (31). Treatment with rifampin has been shown to decrease the level of ROS compared to ceftriaxone in an experimental meningitis model in rabbits (9).…”
Section: Discussionmentioning
confidence: 99%
“…Human observational studies have repeatedly found longterm sequelae after pneumococcal meningitis, including sensomotor deficit, hearing loss, and cognitive impairment, which may occur in up to 30% of surviving patients (202,241,496,497,500,526). Human histopathological data showed that the parenchymal damage was caused by increased ICP, cytotoxic and vasogenic edema, herniation, and local leukocyte infiltration or abscess formation, as well as by cortical necrosis and hippocampal neuronal loss (346,513).…”
Section: Neuronal Damage/histopathologymentioning
confidence: 99%
“…Furthermore, TLR and MyD88 knockout mice demonstrated less hearing loss following pneumococcal meningitis (247). In a rat model, cochlear expression of iNOS and eNOS was upregulated following pneumococcal meningitis, and RNS-mediated cochlear damage could be attenuated both electrophysiologically and histopathologically by RNS scavengers (227,241,243). Earlier studies with guinea pigs showed that local perfusion of the scala tympani with NO donor compounds resulted in cochlear damage and could be attenuated by NO inhibitors or O 2 scavengers (14).…”
Section: Cochlear Damage and Hearing Lossmentioning
confidence: 99%
“…Following entry of pathogens or irritants into the perilymphatic space contamination may progress into the membranous labyrinth and cause inflammation and damage to the cochlear and vestibular end organs. Oxidative stress triggered by the inflammatory process appears to be involved and may lead to cellular damage of hair cells and vestibular cochlear neurons (Abi-Hachem 2010; Klein et al, 2008).…”
Section: Otitis Internamentioning
confidence: 99%